A chiral LC‐MS/MS method for the enantioselective determination of R‐(+)‐ and S‐(–)‐pantoprazole in human plasma and its application to a pharmacokinetic study of S‐(–)‐pantoprazole sodium injection. (7th May 2017) - Jiao, Huiwen; Li, Yueqi; Sun, Luning; Zhang, Hongwen; Yu, Liyuan; Yu, Lei; Yuan, Ziqingyun; Xie, Lijun; Chen, Juan; Wang, Yongqing
Abstract: Pantoprazole, a proton pump inhibitor, is clinically used for the treatment of peptic diseases. An enantioselective LC‐MS/MS method was developed and validated for the simultaneous determination of pantoprazole enantiomers in human plasma. Pantoprazole enantiomers and the internal standard were extracted from plasma using acetonitrile. Chiral separation was carried on a Chiralpak IE column using the mobile phase consisted of 10 mm ammonium acetate solution containing 0.1% acetic acid–acetonitrile (28 : 72, v /v). MS analysis was performed on an API 4000 mass spectrometer. Multiple reactions monitoring transitions of m / z 384.1→200.1 and 390.1→206.0 were used to quantify pantoprazole enantiomers and internal standard, respectively. For each enantiomer, no apparent matrix effect was found, the calibration curve was linear over 5.00–10, 000 ng/mL, the intra‐ and inter‐day precisions were below 10.0%, and the accuracy was within the range of –5.6% to 0.6%. This method was applied to the stereoselective pharmacokinetic studies in human after intravenous administration of S ‐(–)‐pantoprazole sodium injections. No chiral inversion was observed during sample storage, preparation procedure and analysis. While R ‐(+)‐pantoprazole was detected in human plasma with a slightly high concentration, which implied that S ‐(–)‐pantoprazole may convert to R ‐(+)‐pantoprazole in some subjects.